Drosophila Corazonin Neurons as a Hub for Regulating Growth, Stress Responses, Ethanol-Related Behaviors, Copulation Persistence and Sexually Dimorphic Reward Pathways - Ziam Khan; Maya Tondravi; Ryan Oliver; Fernando J. Vonhoff (Journal of Developmental Biology, 2021)
The neuronal mechanisms by which complex behaviors are coordinated and timed often involve neuropeptidergic regulation of stress and reward pathways. Recent studies of the neuropeptide Corazonin (Crz), a homolog of the mammalian Gonadotrophin Releasing Hormone (GnRH), have suggested its crucial role in the regulation of growth, internal states and behavioral decision making. We focus this review on Crz neurons with the goal to (1) highlight the diverse roles of Crz neuron function, including mechanisms that may be independent of the Crz peptide, (2) emphasize current gaps in knowledge about Crz neuron functions, and (3) propose exciting ideas of novel research directions involving the use of Crz neurons. We describe the different developmental fates of distinct subsets of Crz neurons, including recent findings elucidating the molecular regulation of apoptosis. Crz regulates systemic growth, food intake, stress responses and homeostasis by interacting with the short Neuropeptide F (sNPF) and the steroid hormone ecdysone. Additionally, activation of Crz neurons is shown to be pleasurable by interacting with the Neuropeptide F (NPF) and regulates reward processes such as ejaculation and ethanol-related behaviors in a sexually dimorphic manner. Crz neurons are proposed to be a motivational switch regulating copulation duration using a CaMKII-dependent mechanism described as the first neuronal interval timer lasting longer than a few seconds. Lastly, we propose ideas to use Crz neuron-induced ejaculation to study the effects of fictive mating and sex addiction in flies, as well as to elucidate dimorphic molecular mechanisms underlying reward behaviors and feeding disorders.